Toxicity Test of Windu Shrimp (Penaeus monodon) Skin Chitosan With Brine Shrimp Lethality Test Method - Dina Suciati Saragih; Ridwanto Ridwanto; Anny Sartika Daulay; Dikki Miswanda; Haris Munandar Nasution (Indonesian Journal of Chemical Science and Technology (IJCST), 2022)
Chitosan is a modification of chitin compounds that are widely found in the outer skin of crustacean animals such as shrimp and crabs. This research includes isolation of chitin and chitosan: deproteination, demineralization, depigmentation and deacetylation namely transformation of chitin into chitosan, characterization of chitosan, FTIR, and chitosan toxicity test with five concentrations of test solution, namely 100 g/ml, 250 g/ml, 500 g/ml, 750 g/ml and 1000 g/ml using the BSLT method by looking at the number of deaths of Artemia salina L larvae (LC50). The results of tiger prawn shell chitosan (Penaeus monodon) obtained the % degree of deacetylation of 60%. The results of the toxicity test showed that chitosan was not toxic to Artemia salina Leach, indicated by the LC50 value > 1000µg/ml. chitosan windu 4994.16 g/ml, chitosan is not toxic